Konsep Pendidikan Islam Muhammad Abduh serta Implikasinya terhadap Pendidikan Islam di Indonesia - Prasetya, Juni (Institut Agama Islam Negeri (IAIN) Tulungagung, 2018)
The dichotomic view that appears in people's lives has a negative impact on Islamic education in Indonesia. This dichotomic view gives a negative impact likes backwardness and disintegration on Islamic education in Indonesia. In fact, Islamic education in Indonesia has not produce the scholars who have a spiritual and intellectual commitment. Therefore, this research offers the concept of Muhammad Abduh's Islamic education as a solution.This research aims to analyze the concept of Islamic education of Muhammad Abduh and to show the implication of the concept of Islamic education of Muhammad Abduh towards Islamic education in Indonesia. The research used qualitative approach with library study. The data collecting technique used was documentation technique. The data obtained was then analyzed using content analysis. The result of the research indicates that the concept of Islamic thought of Muhammad Abduh was to educate the mind and soul of the students. The implication of Islamic education concept of Muhammad Abduh towards Islamic Education in Indonesia was the objective of the education should pay attention the natural tendency of human being comprehensively. The students, both boys and girls, should increase the knowledge. The educator should have intellectual competences and good religious. The learning method implemented should develop the mind and spiritual aspects (transfer knowledge and transfer value). The Islamic education in Indonesia should learn about the realm of modern knowledge and religious knowledge.